METHODOLOGY OF THE ANALYTICAL SUBSTANTIATION OF STATE FINANCIAL SUPPORT NECESSITY TO THE MANUFACTERS IMPLEMENTED IMPORT REPLACEMENT PROGRAMS - S. M. Hairova; V. A. Kovalyov; B. G. Hairov (Вестник СибАДИ, 2019)
Introduction. Solving the problem of state financial support for commodity producers implementing import substitution programs is becoming relevant in the current economic situation in Russia. The paper briefly describes the options for attracting investment in production and logistics clusters.Materials and methods. The paper uses the methods of synthesis and analysis, system and comparative analysis, expert assessments, principles for constructing economic and organizational structures, problem-oriented and situational approaches. The methodological basis of the study is the works of domestic and foreign scientists in the field of the macro- and mesologistics in the economic system.Results. The technique of analytical substantiation of the state financial support for producers of import substitution programs is presented. A management model for production and logistics clusters to identify the best option for financing investment projects is proposed. Discussion and conclusions. The paper proposes the formation of production and logistics clusters for the initiative to attract investment and support sectors of the national economy, for example, the timber industry complex. Moreover, the necessity of creating territorial  innovation clusters based on the principles of public-private partnership is substantiated. The research demonstrates that it is expedient to form production and logistics clusters in order to proactively attract  investments and to support the industry from the states since investment risks do not attract large investors for the development of the timber industry complex.